Effectiveness Of Self-Instructional Module (Sim) On Paternal Attitude Of Expectant Fathers And Maternal Satisfaction On Perinatal Outcome - Gundluru, Aruna; Armugam, Indira; V, Jayanthi; V, Rupa Saritha Reddy; Mahmmad, Suleman Shareef; Alex, Viji; T, Ushakiran; P M, Smitha (National Journal of Community Medicine, 2022)
Introduction: Paternal involvement (PI) has been recognized to have an impact on pregnancy and infant outcomes. The mother’s satisfaction during the birthing process is the most frequently reported indicator in the evaluation of the quality of maternity services. Male involvement reduces maternal stress increases uptake of prenatal care leads to cessation of risk behaviours and ensures men’s involvement in their future parental roles from an early stage. The aim of the study is to assess the effectiveness of self instructional module paternal attitude towards perinatal outcome and maternal satisfaction on paternal attitude. Methodology: A cross-sectional study was conducted on 320 expectant fathers attending antenatal clinic. A five point rating scale was used to assess the attitude of paternal on pregnancy and labour outcome and Observational check list to assess the postnatal mother satisfaction. Results: The scores were significantly improved after intervention, in the experiment group, in pre-test, the mean score was 78.61 and the post-test mean score was 120.56, the mean difference is 41.95 whereas, in the control group, the mean score of 79.43 and the post-test mean score was 80.25, the mean difference is 0.82. After self instructional module intervention, in experimental group, 81.88% of them are having satisfied, 18.12% of them are having not satisfied. In control group, 48.75% of them are having satisfied level of score, 51.25% of them are having not satisfied level of score. Conclusion: Most fathers were very positive about their partner’s pregnancy. They, however, need to be motivated to use that knowledge into practice.